Wykonywanie tymczasowego aresztowania w ustawodawstwie i polityce penitencjarnej Polski okresu międzywojennego - Pałaszewski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article discusses the issue of the use of temporary arrest in Poland in 1918–1939 in the context of the penitentiary system development. The modern literature distinguishes two main periods in the development of the penitentiary system in Poland. The first period 1918–1928 is characterised by a take-over of prisons from the former occupants of Polish territories. The process was accompanied by the development of legal basis for the functioning of the system to replace the legislation of the three partitioning powers Russia, Prussia and Austria in this domain. The main task at that time was to prepare the infrastructure and train prison staff. The second period 1928–1939 marks the establishment of final and uniform rules of the prison system across Poland, substantial development of the penitentiary system and its adaptation to the global and European trends of that time. The study examines the key legal acts of the inter-war period regulating the execution of temporary arrest.
Keywords: temporary arrest; penitentiary policy; Polish legislation of the inter-war period